2008
DOI: 10.1177/0091270008318006
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐ and Time‐Dependent Pharmacokinetics of Midostaurin in Patients With Diabetes Mellitus

Abstract: Midostaurin is a novel potent inhibitor of both protein kinase C and the major receptor for vascular endothelial growth factor involved in angiogenesis, presenting a rationale for its use in diabetic retinopathy. This study evaluated the safety and pharmacokinetics of midostaurin following multiple oral doses of midostaurin for 28 days at 4 dose levels (25 mg bid, 50 mg bid, 75 mg bid, 75 mg tid), as well as a single oral 100-mg dose in patients with diabetes mellitus (n = 9-13 per dose cohort). Pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 18 publications
(43 reference statements)
1
38
0
Order By: Relevance
“…The non-linear pharmacokinetics of CGP62221 follows the same pattern as that of midostaurin, whereas the second metabolite, CGP52421, rises over time until reaching steady-state concentrations after one month of daily treatment (33)(34)(35)(36)(37). Our data show that CGP52421 is less effective in producing growth inhibition and apoptosis in neoplastic MC when compared to midostaurin.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The non-linear pharmacokinetics of CGP62221 follows the same pattern as that of midostaurin, whereas the second metabolite, CGP52421, rises over time until reaching steady-state concentrations after one month of daily treatment (33)(34)(35)(36)(37). Our data show that CGP52421 is less effective in producing growth inhibition and apoptosis in neoplastic MC when compared to midostaurin.…”
Section: Discussionmentioning
confidence: 55%
“…or 75 mg t.i.d. ), day-28 plasma exposure as assessed by area under the plasma-concentration time curve (AUC), for CGP62221 was slightly higher than that for midostaurin, whereas for CGP52421, the AUC52421/AUCmidostaurin ratio was greater than 5 (37).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistently with this hypothesis, cell viability analysis as a function of treatment with kinase inhibitors showed that CDs+ cases were more sensitive than CDs-to MEKi (at 10, 100 and 1,000nM), FLT3/PKCi (1 and 10μM) and PAKi (1μM) (Figure 1c). These concentrations are physiologically relevant for MEKi and FLT3/PKCi 8,9 .…”
mentioning
confidence: 99%
“…Some of the reported PKC inhibitors are mentioned in Table 1, viz. Midostaurin (PKC412, CGS41251, N-benzoyl staurosporine), UCN-01 (KW-2401, NSC-638850), Lestaurtinib (CEP-701, KT-5555), Ro-31 --8220 and Go6976 [41][42][43][44][45][46].…”
Section: Inhibitors and Structure--activity Relationship (Sar) Studymentioning
confidence: 99%